THE MARGIN IN THE SPEECH OF MAGIC REALISM - Bashir Thabet Mohammed Al-Anzi; Latif Mahmoud Mohamed Al Ghurairy (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The writer and poet depend on a certain rule on which he is based to edit his creative texts with the available tools to help him in that production. And as the world around us is in a state of change which made the writer keep pace with those changes to extend to literature and showing each transition adopting a thought and vision of its own, which resulted in the idea of the center and the margin. Everything that was excluded by a particular doctrine is embraced by another one. It is necessary that some things will be selected and others will be neglected. This study dealt with the issue of marginal and accidental in the discourse of literature, after the writer felt the need to pay attention to everything that is rejected in the custom of previous literary cultures and attention to the trivial and neglected elements. The magical realism embraces what is magical, fantastical and mythical which has become the basic rule of this literary current .